ENVIRONMENTAL ACCOUNTING AND PROFIT PERFORMANCE OF QUOTED OIL AND GAS COMPANIES IN NIGERIA (American Journal of Interdisciplinary Research and Development, 2024)
This paper examined the relationship between environmental accounting and the profit performance of listed oil companies and gas companies in Nigeria for a period of 5 years, 2013-2007. The secondary data from the annual report and accounts of five (5) quoted oil and gas companies were used for the analysis to test the formulated hypotheses. The multiple linear regression was the statistical tool used for the analysis, done by e-view 10. The proxy for the independent variable; environmental accounting used is, environmental remediation and pollution control costs white gross profit margin was the proxy for dependent variable; profit performance. The stationary test shows that the variables are stationary at the first difference. The co-integration test proved the presence of a long run relationship. The granger causality test proved no causality between the variables and after testing the hypotheses the variables showed a statistically significant relationship with each other. The paper recommends that, it is essential that oil and gas companies avoid violating environmental legislation to avoid their sanctions, which may adversely affect their profits, and the management of oil and gas companies must have a positive disposition towards cost-effective practices and environmental projects to restore and guarantee stable and sustainable operations in the Nigerian oil sector.